Analysis of the Process of Recruitment, Selection and Hiring of Collaborators in Long Stay Establishments for the Elderly (ELEAM) in Chile - Traverso, Pedro; Saldías, Francisca; Dillarza, Juan (Estudios de Administración, 2022)
The accelerated aging of the population highlights the importance of countries preparing to care for and assist the elderly. The Long-Stay Establishments for the Elderly (ELEAM) are a fundamental piece in this care, and the people who work there are decisive in the quality of the service, attention and affection that is provided to the residents. Consequently, the recruitment, selection and hiring of these collaborators is essential. Through a literature review, a field study, and a survey, we identified several opportunities for improvement in this process. These opportunities were grouped into three categories: general improvements, improvements in the recruitment and selection process, and improvement in the retention of good employees. We believe that the analysis and eventual implementation of these opportunities could improve the skills, knowledge, and abilities of ELEAM’s collaborators, improving the quality of the service they provide to older adults.